Design and performance of 20 watts portable solar generator - Abdul Majid, Zafri Azran; Hazali, Norazlanshah; Hanafiah, M. A. K. M.; Abdullah, A. A.; Ismail, Ahmad Faris; Ruslan, M. H.; Sopian, K.; Mohd Azmi, M. S. (2011)

(untitled)
A new portable solar generator has been developed to generate electricity. It has the potential to replace petrol generator, widely used by peddlers at night markets (pasar malam). Conventional generators are heavy, oily, have high maintenance and use fossil fuel to generate electricity. The solar generator can generate 20 Watts of electricity. This amount of power can supply up to 96 hours of electricity for the purpose of lighting and running small electrical appliances. The power output is (alternating current) AC current using 150 Watts inverter with 200 Watts surge, suitable for all commercial single phase electric appliances. Solar charge controller is used to maximize the charging rate and to protect the battery. The system has low maintenance whereby the batteries need to be changed every three to four years, depending on the usage. The main concepts of portable solar generator are to reduce installation cost and to introduce a compact design of an optimal energy sizing system. The materials used to develop the solar generator can be easily obtained from local markets, thus reducing the cost of developing the system and making it suitable for commercialization.